Mapping Project-Based Learning E-Modules: A Bibliometric and Systematic Literature Review - Asa Dyah Ayu Nuralita; Bambang Subali; Sunyoto Eko Nugroho; Wiyanto, Wiyanto; Mohd Yusof, Mohammad Mubarrak (Jurnal Inovasi Pendidikan IPA, 2025)
Electronic modules (e-modules) are widely used learning media that support both classroom and independent study. They offer an alternative for students to learn at home and have evolved by integrating various learning models, including project-based learning (PjBL). This study aims to reveal research trends in the development of PjBL-integrated e-modules from 2016 to 2025 using the PRISMA method. Article data were collected systematically through the Publish or Perish tool on Google Scholar with keywords such as “development,” “electronic module,” “e-module,” and “project-based learning.” From 344 initial articles, 92 met the inclusion criteria for content analysis, and 51 were selected for analysis based on keyword relevance, complete metadata, and citation data. These were visualized using VOSviewer. The results indicate that PjBL-integrated e-modules have significant potential to improve student learning outcomes and engagement. In addition to academic insights, this research offers practical contributions. For teachers, it presents a clear model for implementing interactive, contextualized science learning. For curriculum developers, it provides strategies for integrating 21st-century skills and independent learning into digital tools. Overall, the findings support the development of adaptive, student-centered learning materials aligned with current educational needs